2014
DOI: 10.1016/j.matbio.2014.06.005
|View full text |Cite
|
Sign up to set email alerts
|

WDR72 models of structure and function: A stage-specific regulator of enamel mineralization

Abstract: Amelogenesis Imperfecta (AI) is a clinical diagnosis that encompasses a group of genetic mutations, each affecting processes involved in tooth enamel formation and thus, result in various enamel defects. The hypomaturation enamel phenotype has been described for mutations involved in the later stage of enamel formation, including Klk4, Mmp20, C4orf26, and Wdr72. Using a candidate gene approach we discovered a novel Wdr72 human mutation in association with AI to be a 5-base pair deletion (c.806_810delGGCAG; p.G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 62 publications
3
63
0
1
Order By: Relevance
“…This pattern suggests that the endocytosis mechanism, in the absence of KLK4, is still able to reabsorb much of the protein near the enamel surface, but the protein away from the surface is unable to work its way back to the cell for reabsorption. Interestingly, a pathological accumulation of enamel proteins also occurs in Wdr72 −/− mice, whose enamel shows more severe reductions in mineral density and hardness than those observed in Klk4 −/− mice [45,46]. WDR72 is an intracellular protein and defects in WDR72 contribute to the etiology of autosomal recessive amelogenesis imperfecta [47,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pattern suggests that the endocytosis mechanism, in the absence of KLK4, is still able to reabsorb much of the protein near the enamel surface, but the protein away from the surface is unable to work its way back to the cell for reabsorption. Interestingly, a pathological accumulation of enamel proteins also occurs in Wdr72 −/− mice, whose enamel shows more severe reductions in mineral density and hardness than those observed in Klk4 −/− mice [45,46]. WDR72 is an intracellular protein and defects in WDR72 contribute to the etiology of autosomal recessive amelogenesis imperfecta [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…WDR72 is an intracellular protein and defects in WDR72 contribute to the etiology of autosomal recessive amelogenesis imperfecta [47,48]. Identification of proteins that co-immunoprecipitated with WDR72 suggested that WDR72 is involved in endocytosis or vesicle trafficking [45,46]. These findings, and the discovery that Klk4 is a recent (evolutionary) addition to the process of enamel maturation, suggest that endocytosis is the primary mechanism for the removal of enamel matrix proteins and that secretion of the KLK4 enzyme is a later refinement that facilitates that process by degrading extracellular proteins and thereby allowing proteins in the deeper layers to more rapidly diffuse to the enamel surface and be reabsorbed by ameloblasts.…”
Section: Discussionmentioning
confidence: 99%
“…2012; Katsura et al. 2014). All of the mutations are located sporadically throughout the gene (exons 8, 10, 12, 15, 16, and 17) and truncate the protein (either nonsense or frameshift mutations) if translated.…”
Section: Discussionmentioning
confidence: 99%
“…2012; Katsura et al. 2014), the functions of WDR72 and its role in enamel maturation remain largely unknown. Human WDR72 encodes an intracellular protein of 1102 amino acids with no known functional domains except a β -propeller structure composed of WD40 repeat domains in its N-terminus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation